Dampak Pendapatan dan Pengalaman Keuangan Terhadap Kesejahteraan Keuangan Keluarga Melalui Literasi Keuangan - Astuti, Fitria Yuni; Gilang Kharisma (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
The purpose of this study was to examine the effect of income and financial literacy on family financial well-being. In addition, we will also examine the effect of financial experience as a mediation variable. In this study we use quantitative research method approach in solving the above problems. For sampling criteria, we use a purposive sampling approach in the sampling technique, where later the samples taken will be filtered based on certain criteria. We used simple criteria in this study, namely all married students of the faculty of economics and business. Based on these criteria, a sampling of 72 respondents was selected. At a private campus in Kendal district. Based on the analysis of the data that has been submitted above. Financial literacy variables are not proven to affect family financial well-being, while other hypotheses are acceptable, such as income variables proven to affect family financial well-being, financial experience variables, proven to affect family financial well-being and financial experience variables proven to affect financial literacy. The role of financial literacy is proven to mediate the relationship of financial experience variables to family financial well-being variables.